Molecular epidemiology of HIV-1 in Oryol Oblast, Russia. Issue 1 (1st June 2022) - Safina, Ksenia R; Sidorina, Yulia; Efendieva, Natalya; Belonosova, Elena; Saleeva, Darya; Kirichenko, Alina; Kireev, Dmitry; Pokrovsky, Vadim; Bazykin, Georgii A
Abstract: The HIV/AIDS epidemic in Russia is growing, with approximately 100, 000 people infected annually. Molecular epidemiology can provide insight into the structure and dynamics of the epidemic. However, its applicability in Russia is limited by the weakness of genetic surveillance, as viral genetic data are only available for <1 per cent of cases. Here, we provide a detailed description of the HIV-1 epidemic for one geographic region of Russia, Oryol Oblast, by collecting and sequencing viral samples from about a third of its known HIV-positive population (768 out of 2, 157 patients). We identify multiple introductions of HIV-1 into Oryol Oblast, resulting in eighty-two transmission lineages that together comprise 66 per cent of the samples. Most introductions are of subtype A (315/332), the predominant HIV-1 subtype in Russia, followed by CRF63 and subtype B. Bayesian analysis estimates the effective reproduction number Re for subtype A at 2.8 [1.7–4.4], in line with a growing epidemic. The frequency of CRF63 has been growing more rapidly, with the median Re of 11.8 [4.6–28.7], in agreement with recent reports of this variant rising in frequency in some regions of Russia. In contrast to the patterns described previously in European and North American countries, we see no overrepresentation of males in transmission lineages; meanwhile, injecting drug users are overrepresented in transmission lineages. This likely reflects the structure of the HIV-1 epidemic in Russia dominated by heterosexual and, to a smaller extent, people who inject drugs transmission. Samples attributed to men who have sex with men (MSM) transmission are associated with subtype B and are less prevalent than expected from the male-to-female ratio for this subtype, suggesting underreporting of the MSM transmission route. Together, our results provide a high-resolution description of the HIV-1 epidemic in Oryol Oblast, Russia, characterized by frequent interregional transmission, rapid growth of the epidemic, and rapid displacement of subtype A with the recombinant CRF63 variant.